Much ado about nothing? In discussion with the study of Evert-Jan Viedder: " Conflict in the miracle stories in Matthew 8 and 9: A sociological and exegetical study" - Joubert, Stephan (Hervormde teologiese studies, 1995)
This essay is a brief evaluation of Evert-Jan Viedder's study of conflict in the miracle stories in Matthew 8 and 9. His use of his own conflict model to interpret the conflict between Jesus and the leaders of Israel which is reflected in Matthew 8 and 9, and which at the same time serves as a transparency for the conflict between the community of Matthew and the Pharisees in the post-AD 70 period, is discussed critically in terms of his epistemological perspectives and methodological procedures.